The Structural and Administrative Demands of Unwritten Constitutional Principles - Berger, Kate (McGill Law Journal / Revue de droit de McGill, 2019)
This article challenges the traditional view in administrative law scholarship that the mandate and design of administrative decision-makers are principally products of executive policy choice and legislative delegation. Drawing on public law theories of structural interpretation and positioned within the growing field of administrative constitutionalism, this article argues that unwritten features of the Constitution can make concrete demands on institutional structure and tribunal design such that certain functions and features of the administrative state are constitutionally required. The argument emerges from a careful analysis of a single case study, that of the discipline, and in particular the removal, of superior court judges in Canada. The analysis reveals that section 99(1) of the Constitution Act, 1867 provides an incomplete account of the procedures that must be followed in order to remove a federally appointed judge from the bench. More specifically, the case study establishes that the principle of judicial independence requires that judges be eligible for removal under section 99(1) only after an administrative process is held, one that investigates the alleged misconduct and assesses the facts against the constitutional standard of good judicial behaviour. Judicial independence further demands that this process embody certain essential features—features that are familiar to administrative law: the inquiry must be carried out by a body that is independent from the political branches of government; the body must conduct itself in accordance with a commitment to the independence of the judiciary; the inquiry must be carried out in accordance with the duty of fairness; and both the process and substantive determinations of the inquiry process must be subject to review by the courts. While current theories of administrative constitutionalism have often been focused on the role of administrative decision-makers in interpreting and implementing constitutional rights, this article builds on the work of Mashaw, Lee, Bremer, and Metzger and Stack to open and contribute to important structural conversations in the field.